Sanciones establecidas para el delito de violencia psicológica que causen un daño severo no guardan relación con el principio de proporcionalidad - Shiguando Andi, Rodolfo Edgar (2017)
Article 157 of the Code of Criminal Integral Penal Code criminalizes and punishes "A person who, as a manifestation of violence against women or members of the family, causes harm to the mental health by acts of disturbance, threat, manipulation, blackmail, humiliation, Isolation, surveillance, harassment or control of beliefs, decisions or actions, "the psychological offense against the woman or member of the family nucleus, when it causes harm to mental health, and this is determined by the ability of each person to dispose of or general resources To deal with the conflictive situations that arise in the family nucleus. Psychological violence involves the alteration of part of the aggressor with psychological attacks, which in the victim is left in situations of psychic destitution, without protection or resources. According to Art. 157 numeral 3 of the Code of Criminal Integral, it indicates that psychological violence against the woman or member of the family nucleus will be sanctioned: "If the cause of the severe psychological damage that even with the specialized intervention has not been able to reverse will be Punishable by a term of imprisonment of one to three years, "these refer to the consequences of the abuser due to verbal abuse, but their damage is severe or eternal, but with psychological damage, which is a disturbance to the balance Permanent mental illness of a pathological nature, a fact that alters the personality to the balance regulated by the reasoning and the intellectual faculties of the human person and causes a psychic and mental incapacity. Indicates the severe, illicit psychological damage that becomes permanent, which causes in the person an impression or neurological imprint on the nervous system, referred to the suffering of nerves. This system can be divided into two main groups: "1. Cerebral system; And, 2. Neurovegetative system. Taking into account that the manifestation of violence causes a severe mental injury, it is to be understood that it is irreversible, in which it is indicated that the aggressor will be punished with a custodial sentence of one to three years, Which I believe violates the principle guaranteed in Article 76 numeral 6 of the Constitution of the Republic of Ecuador, in which the "law must establish the proportionality between infractions and criminal sanctions," is thus that the legislator had to establish a higher penalty in The penal private penalty, because it causes permanent damage, as the psychological damage is severe, being a fact that transcends the right to freedom guaranteed in Article 66 numeral 3 of the same constitutional norm of the right to personal integrity, Which includes a life free of violence in the public and private spheres. In this sense, severe psychological damage becomes a malice that leaves a human being disabled for life, as well as neuronal involvement, has neither cure nor treatment, which is a serious crime, which the aggressor must remedy With the indemnification of damages and with the fulfillment of a greater sanction to the one indicated in Art. 157 numeral 3 of the Integral Criminal Code.